THE RELATIONSHIP BETWEEN THE LOCALIZATION OF LABIAL ARTERIES USING ULTRASONOGRAPHY FOR LIP AUGMENTATION PROCEDURES: A LITERATURE REVIEW: 1º LUGAR NA CATEGORIA FORUM IN ENGLISH I - Veloso, Camille de Sousa; Silva Filho, José Evando da; Ximenes, Sandra Régia Albuquerque; Viana, João Paulo; Albuquerque, Danielle Frota (Brazilian Journal of Case Reports, 2024)
Introduction:Lips, being among the most prominent facial features, have hyaluronic acid fillers as one of the most commonly used procedures to enhance their shape and volume. However, these procedures can present complications, many of which are related to injury to the labial arteries. The superior labial artery (SLA) and inferior labial artery (ILA) of the lips originate from the facial artery and cross various layers of the lips. Objective: The aim of this study is to conduct a literature review on the relationship between the localization of the superior and inferior labial arteries using ultrasonography as a method in the context of lip augmentation. Methodology: For that, a search was conducted in the "Pubmed'' database using the descriptors “labial artery anatomy” AND “ultrasonography” in English, considering articles published in the last 5 years. Finding 23 results, of which 3 articles were selected, including clinical research articles and excluding the ones that didn't fit the scope of this work. Literature Review:The analyzed studies presented conflicting results regarding the location of labial arteries, differing in their recommendations for injection sites, with a preference for superficial locations in the mucosal and submucosal planes as the safest locations. All of them used ultrasonography to obtain more precise numbers on artery positioning.Conclusion:As suggested by the analyzed studies, when performing various non-invasive cosmetic procedures, ultrasound-guided injections minimize the occurrence of side effects and can provide good safety and efficiency.